Evaluasi Kadar Senyawa Fenolat, Flavonoid Total, serta Aktivitas Antioksidan Secara in vitro dalam Ekstrak Metanol Bawang Dayak (Eleutherine palmifolia (L.) Merr : Evaluation of Phenolic Compounds, Total Flavonoid Content and in vitro Antioxidant Activity of Methanol Extract of Dayak Onion Bulbs (Eleutherine palmifolia (L.) Merr - Farida Laila; Ika Resmeliana; Wina Yulianti; Atep Dian Supardan (KOVALEN: Jurnal Riset Kimia, 2022)
Dayak onion bulbs are a plant originating from Kalimantan which has been used for generations to treat various diseases. This plant is quite easy to grow and develop in many places in Indonesia. The aims of the present study were to evaluate the antioxidant potential of the methanol extract of Dayak onion bulbs based on the total of the phenolic and flavonoids contents and also the antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging ability, ferric reducing power and total antioxidant capacity. The results showed the total phenolic and flavonoid methanol extract of Dayak onion bulbs were 14.49 ± 1.42 mg GAE/g dry weight and 5.41 ± 1.01 mg QE/g dry weight, respectively. Antioxidant activity as measured by the DPPH, total antioxidant capacity, and ferric reduction assay with IC50 values of 16.95 ± 1.58 μg/mL, 24.22 ± 2.51 µg/mL, and 85.40 ± 16.88 µg/mL, respectively. These results suggest that the methanol extract of Dayak onion bulbs has potential bioactive compounds with good antioxidant activity and can be developed as an effective and safe source of natural compounds for functional food or herbal medicine.